Hydrochemical Evaluation of the Tigris River from Kut to Amara sites, Iraq - Al-Sekar, Hala Mohammed; Al-Dabbas, Moutaz (Iraqi Journal of Science, 2022)
The Tigris River is one of the longest rivers in Western Asia and runs through heavily populated areas, especially in Kut and Amara Cities, with nearly 8 million inhabitants. Due to the climatic change and altering the upstream hydrological conditions along the Tigris River, its discharge has severely declined in the last decade, combined with the climate change impact. Hence, studying the impact of climate change on the river and decreasing the annual flow is vital to understand their effect on the river water quality between Kut and Amara sites.  The data of this study covers annual flow conditions of the Tigris River, the total dissolved solids (TDS), and the main ions on monthly bases for the period 2005-2010 for the two sites: Kut and Amara. These data were used to establish the relationships between water discharge (m3/sec) with total dissolved solids (mg/l) and main cations (Na+, Ca2+, Mg2+, and K+) and anions (Cl‾, SO42, HCO3‾). The Climatological data for 1980-2020 show that the annual rainfall values for Kut and Amara sites range between 301-577 mm and 69-200 mm respectively. The annual mean minimum temperature of the Kut ranges between15.7-18.8Co. For Amara, it ranges between 16.6-20.7 Co. It is noticed that the rainfall values of both sites decreased over time, and the temperature is constantly increasing due to the climate change effects over the years. The average annual flow of the Tigris River at Kut site ranged from 13 to 367 m3/sec with an average of 233.2 m3/sec, and for Amara ranged between         22 and 101 m3/sec with an average of 50.2 m3/sec.  The mean annual TDS ranged from 466 to 1150 mg/l, with an average mean annual 758.30 mg/l for Kut station. For Amara, it is ranged between 634 and 2075 mg/l with an average of 1168.61 mg/l. The decrease in the Tigris River discharge affects the chemistry. Calcium, magnesium, and sulfate ions in Kut station are dominated. While at Amara, sodium and sulfate ions are dominant. Such variation is related to the decrease in the Tigris River discharge and the effect of the dissolution of ions from the geological outcrops by the action of natural waters. Moreover, the entry of the transported dissolved load, the city’s sewage, and the agricultural lands’ water that flows into the river increase as the transportation distance increase from Kut to Amara.